Tracked Changes. Textiles. Quantitative chemical analysis. Mixtures of viscose or certain types of cupro or modal or lyocell with flax fibres (method using formic acid and zinc chloride) Part 22, (17th December 2021) - British Standards Institution,
No abstract available